Important Species in Tampa's Urban Forest - Michael G. Andreu; Melissa H. Friedman; Robert J. Northrop (EDIS)
FOR-205, a 4-page illustrated fact sheet by Michael G. Andreu, Melissa H. Friedman, and Robert J. Northrop, presents the information gained about tree species results from an urban ecological assessment conducted in the city of Tampa, including native vs. non-native and invasive tree species, palms and palm diseases, and mangrove forests. Includes references. Published by the UF School of Forest Resources and Conservation, February 2009.